Identifying Jews: The Legacy of the 1941 Exhibition, "Le Juif et la France" - Raymond Bach (Studies in 20th & 21st Century Literature, 1999)
During the Occupation there was a two-pronged effort to separate the Jews from the rest of the French population...
Keywords: 1941 exhibition; 1941; Le Juif et la France; Jews; identity; the Occupation; propaganda; body; embodiment; signifier; reality; creation of reality; Dreyfus; discrimination; racism; ant-Semitism; cinema; Modiano; racist discourse; racial difference; Institut d' Etudes des Questions Juives (IEQJ); Nazism